Ежик в тумане - Козлов Сергей Григорьевич (Самые лучшие сказки, 2017)
Экземпляры: (20180904) / Инвентарный номер: 49949 / Цена: 402.00 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: К 59 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=411.2)6